Research of Useful Properties of Milk Whey and Volume of Whey Is Produced in the Republic of Uzbekistan - Tosheva Durdona Omon qizi; Prof. Akramova R.R. (Academia One, 2023)
Many people don't know that serum is one of the most healing blessings. Its benefits for the body are no less than from cottage cheese, cheese, yogurt and yogurt. The healing properties of yogurt whey were first discovered by the famous Greek scientist Hippocrates. This article contains information aimed at revealing such healing properties of yogurt whey.
Keywords: Statistical information; whey; cheese